Individual and Society in Lu Xun’s Works: A Journey from Tradition to Modernism - Kiriktaş, Ali (Cappadocia Journal of Area Studies, 2024)
Lu Xun is one of the most prominent writers in modern Chinese literature. He addresses the conflicts between traditional societal structures and modernization, focusing on themes such as individual freedom, modernization, and social criticism. Beyond his literary career, Lu Xun left a significant impact on Chinese society as an intellectual. His exposure to Western civilization led him to realize how backward Chinese society had become, prompting him to raise awareness of this backwardness through his works. He critiqued many aspects of society, particularly the feudal social structure and patriarchal family systems, highlighting their negative effects on individuals and advocating for China’s modernization. After recognizing the decay within Chinese society, Lu Xun decided to abandon his medical studies in favor of literature, emphasizing that if society is corrupt, minds must be treated before bodies. Because his works contributed to the intellectual foundation of ideological movements and the Cultural Revolution, Lu Xun greatly influenced Mao Zedong. His writings supported the Cultural Revolution by instilling a revolutionary spirit and promoting the intellectual independence of the people, leading to profound changes in Chinese society. In this sense, Lu Xun’s impact extended beyond influencing writers; he also had a lasting effect on politicians. Through his works Notes Under the Lamp and Wild Grass, Lu Xun delves deeply into the internal conflicts faced by individuals dealing with societal pressures and the process of modernization. In these two works, he explores individuals’ search for identity and their struggles against traditional societal norms. His simple yet powerful language strengthens the social criticism in these works, which provided intellectual contributions to China’s modernization. Through an analysis of the tensions between individuals and society in Notes Under the Lamp and Wild Grass, this paper will examine Lu Xun’s significance in the modernization process.